Tax Compliance in Indonesia: A Meta-Analysis - Titaailla, Verta Arbaath; Fidiana, Fidiana (Finance & Economics Review, 2023)
Purpose: This study aims to summarize existing research ﬁndings regarding the determinants of tax compliance in Indonesia by using Meta-analysis. Methods International databases (Scopus) and Indonesian-accredited journals (Sinta 2) are employed to collect data. A targeted search is conducted using the keyword “compliance” in connection with tax compliance, tax avoidance, tax evasion, and related terms. We used Harzing’s Publish application in searching for related papers. We begin with an initial sample of 71 meta-analyses and finally have 39 studies as the final sample of our literature review. Results: We found that a penalty is not the best way to solve compliance issues. In contrast to the traditional (enforcement) paradigm, our investigation revealed that sanctions could not fully explain compliance. Taxpayers should not feel heavily penalized when there is a delay in reporting. Sanctions that are low and less tangible make taxpayers underestimate existing sanctions. Furthermore, tax reform policies such as the Sunset policy (SP), are not regular provisions that are used consistently. SP is a particular tax policy that eliminates tax penalties for individual taxpayers who have recently registered and amended their tax returns. Implications: This study has substantial implications for the Directorate General of Taxes (GDT) concerning the policy approaches in dealing with tax non-compliance. The Indonesian tax authority needs to shift from sanction to voluntary compliance by framing a friendly approach in dealings with taxpayers. Originality: To our knowledge, this is the first study to review the determinants that influence tax compliance specifically in Indonesia using a meta-analysis lens. Limitations: Some important studies are not accessed because of budget limitations.